O estágio curricular na formação inicial de professores de educação física no estado de Mato Grosso - Almeida, Francisca Franciely Veloso de (2015)
This research has as general aim to know the teacher's and student's perception about the contribution of the Curricular Internship of the graduation courses in Physical Education in the state of Mato Grosso to the formation of the future teacher, as well as how the disciplines of Curricular Internship are structured and organized in the referred courses. To do so, we elaborated a theoretical reference which approaches some historical elements, legal determinants, principles and conceptions of teacher formation. Regarding the formation in the field of Physical Education, we discoursed about the historical trajectory, conceptions and the relation of teacher's knowledge and teacher formation. The research characterizes itself as descriptive with qualitative approach, the data treatment was by interpretive analysis and it did not aimed the quantification of them. The universe of the research was composed by 10 institutions that have a Bachelor’s degree course of Physical Education in the state of Mato Grosso, participating as subjects twenty-four (24) teachers who teach the disciplines of Curricular Internship and a hundred and fifty-four (154) academics. As instruments of research we made a documental analysis of the programmes of the disciplines of Curricular Internship provided by the institutions, from the syllabus, objectives, contents, methodologies and evaluation; semi-structured interview was made with the teachers who teach the discipline of Curricular Internship and questionnaire having fourteen (14) questions, being three (3) closed questions, four (4) closed questions with possibility of justifying and seven (7) open questions, each of them directed to the academics enrolled in the last discipline of Internship or having coursed 50% of the Internship disciplines. About the programmes of disciplines, all the courses fulfilled the minimum necessary hours of 400 hours, legally demanded, being that in three (3) institutions the hours exceeded, the highest hours is 480 hours. Besides the levels of education, yearly Education, Elementary Education and High School, some courses extend the Internship to Youth and Adult Education, Special Education and Schools Programmes. From the interview, we identified that most teachers present satisfaction in teaching the discipline of Internship. About the students’ learning, few recognize as something that is constructed and meaningful, there are groups that value the experience and the direct contact with the doing in practice, some value the knowledge coming of courses, readings and books and there are those who recognize that the relation with the pairs is also a way of learning of the teacher’s work. Most academics consider the Internship disciplines important, because of the approximation with the school’s reality, as well as signing the pretension of acting in teaching in Basic Education. The study observed an advance in the process of structure and organization of the Internship in teacher formation. The achievement of seminars which count with participation of school teachers and presentation of academics’ productions, socializing the knowledge built by everyone from the Internship. At last, we presuppose that knowing the different forms and configurations of Internship in the bachelor’s degree course of Physical Education, we may contribute, highlighting its limits, possibilities and what has been constructed in this formative space